GAMBARAN PSYCHOLOGICAL WELL-BEING MANTAN NARAPIDANA - Azani, Azani (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2012)
AbstractThis study aims to describe the dimensions of psychological well-being offormer inmates. Study was conducted in one of the areas in Yogyakarta SpecialProvince, the City of Yogyakarta. The approach used in this study is a casestudy. The method of data collection used interviews and observations. Thesubjects of this study are 3 participants. The data analysis that used in thisstudy is content analysis. Based on the research, subject A has not shown selfacceptance dimension, but on the subject of B and C have shown the existenceof self-acceptance, when the subject was shown a positive relationships withothers, the dimensions of autonomy has not been demonstrated by the threesubjects, the subjects A and B has not shows the dimensions of environmentalmastery, but the subject of C have shown these dimensions, three subjectshave shown the dimension of interest, and three subjects has also shown thedimension of personal growth.Keywords : psychological well being, ex-convict